2021
DOI: 10.3389/fimmu.2021.800268
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Risk Model and Tumor Immune Environment Modulation of m5C-Related LncRNAs in Pancreatic Ductal Adenocarcinoma

Abstract: RNA methylation modification is a key process in epigenetics that regulates posttranscriptional gene expression. With advances in next-generation sequencing technology, 5-methylcytosine (m5C) modification has also been found in multiple RNAs. Long non-coding RNAs (lncRNAs) were proved to have a key role in cancer progression and closely related to the tumor immune microenvironment. Thus, based on the PDAC patients’ clinical information and genetic transcriptome data from the TCGA database, we performed a detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…What roles do m5C-related lncRNAs play in the TME? In pancreatic ductal adenocarcinoma, m5C-related lncRNAs have been reported to induce polarisation or infiltration of M2 phenotype macrophages [ 26 ]. In this research, we investigated the relationship between m5C-related lncRNAs and tumor immune cell infiltration in STAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What roles do m5C-related lncRNAs play in the TME? In pancreatic ductal adenocarcinoma, m5C-related lncRNAs have been reported to induce polarisation or infiltration of M2 phenotype macrophages [ 26 ]. In this research, we investigated the relationship between m5C-related lncRNAs and tumor immune cell infiltration in STAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen m5C methylation-regulated genes have been described in the published study, namely, YBX1, ALYREF, DNMT1, NSUN4, TRDMT1, TET2, NSUN7, NSUN6, NSUN5, NSUN3, NSUN2, DNMT3A, and DNMT3B [ 26 ]. The expression matrix of the 13 m5C methylation-regulated genes was obtained from RNA-seq transcriptome data.…”
Section: Methodsmentioning
confidence: 99%
“…lncRNA H19 modified by m5C methylation promotes hepatocarcinogenesis and progression through recruitment of oncoprotein G3BP1 ( 55 ). Recently, deep bioinformatics mining of high-throughput data revealed that m5c-related lncRNAs have potential effects on immune infiltration and can be used as multiple tumor prognostic markers and therapeutic targets ( 56 , 57 ). To our knowledge, this is the first exploration of m5C-related lncRNAs in LGG, yielding the prognostic biomarkers LINC00265, CIRBP-AS1, GDNF-AS1 and ZBTB20-AS4.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic variation predicts the risk of tumor development and growth, and the DNA methylome in PDAC is significantly altered from healthy controls, with several protein coding genes and long non-coding genes being potential prognostic biomarkers [36,37]. In addition, long non-coding RNAs (lncRNAs) and microRNA expression profiles may help prognosticate patients [38,39]. For one, microRNA-192 is epigenetically downregulated in PDAC via promoter methylation, where higher expression caused better overall survival, together with in vitro data suggesting an inverse correlation with EMT markers and less favorable growth patterns [40].…”
Section: Epigenetic Changes In Pdacmentioning
confidence: 99%